Virtual Heterotopias and the Contested Histories of Kowloon Walled City. Issue 6 (September 2022) - May, Lawrence
Hong Kong's Kowloon Walled City has found new life in videogames during the three decades since its demolition, taking on unstable and sometimes contradictory forms when reimagined through virtual architecture. At stake in these acts of memory are the historical discourses surrounding everyday life in Kowloon Walled City, its uncertain political and cultural status, and ongoing postcolonial debates concerning Hong Kong identity. I analyze Kowloon's Gate, Shenmue II, and Mr Pumpkin 2: Walls of Kowloon to uncover the contestation of the city's histories through the types of spaces Michel Foucault described as heterotopic: at once real and unreal, and existent and non-existent. This analysis reveals the fluid nature of cultural memory and historical discourse in videogame spaces, as well as how virtual spatiality and the past can be used together to understand and define the present.